Integrasi Konsep Hukum Karmaphala dalam Pembentukan Moral dan Etika Anak Usia Dini - Indrayasa, Kadek Bayu (Fakultas Dharma Duta dan Brahma Widya, 2024)
The role of the concept of Karmaphala Law in the perspective of moral and ethical formation in early childhood. The concept of Karmaphala Law, which originates from Hindu tradition and Hindu philosophy, provides a strong philosophical basis for understanding the principle of cause-and-effect law in every action. By exploring this principle, this research aims to explore how this concept can be integrated into the moral education curriculum for early childhood. This research uses a literature review method. The importance of applying the concept of Karmaphala Law in environmental and sustainability education. This concept can help children understand the connection between their actions and the environment, stimulate a sense of responsibility towards nature, and support the development of positive character and ethics. The result of this research is that the integration of the Karmaphala Law concept in the moral education curriculum for early childhood is not only relevant but also has a positive impact in shaping the morals and ethics of early childhood. The application of this concept provides a strong foundation for the formation of a future generation that is responsible, morally aware and cares about the surrounding environment.